2015
DOI: 10.1038/oncsis.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorylated prodrug FTY720 is a histone deacetylase inhibitor that reactivates ERα expression and enhances hormonal therapy for breast cancer

Abstract: Estrogen receptor-α (ERα)-negative breast cancer is clinically aggressive and does not respond to conventional hormonal therapies. Strategies that lead to re-expression of ERα could sensitize ERα-negative breast cancers to selective ER modulators. FTY720 (fingolimod, Gilenya), a sphingosine analog, is the Food and Drug Administration (FDA)-approved prodrug for treatment of multiple sclerosis that also has anticancer actions that are not yet well understood. We found that FTY720 is phosphorylated in breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 55 publications
4
102
0
1
Order By: Relevance
“…In this study, FTY720 was given orally to mice in clinically accepted doses and, as a result, HDAC activity decreased and the evolution and development of breast tumors were diminished (110). They also found that the inhibitor sensitizes cells to tamoxifen and, in comparison with other HDAC inhibitors (e.g.…”
Section: Sk7041mentioning
confidence: 67%
See 1 more Smart Citation
“…In this study, FTY720 was given orally to mice in clinically accepted doses and, as a result, HDAC activity decreased and the evolution and development of breast tumors were diminished (110). They also found that the inhibitor sensitizes cells to tamoxifen and, in comparison with other HDAC inhibitors (e.g.…”
Section: Sk7041mentioning
confidence: 67%
“…They also found that the inhibitor sensitizes cells to tamoxifen and, in comparison with other HDAC inhibitors (e.g. SAHA), it enhanced the sensitivity to the treatment (110).…”
Section: Sk7041mentioning
confidence: 91%
“…FTY720 is phosphorylated in the nucleus by SphK2 and FTY720-phosphate, a potent class I HDAC inhibitor that facilitates fear extinction memory in mice (36). In addition, FTY720 also activates estrogen receptor (ER)- expression to enhance hormonal therapy for breast cancer (37).…”
Section: S1p a Lipid Mediatormentioning
confidence: 99%
“…Recent studies suggest that S1P generated from SphK2, may promote cancer cell proliferation and migration, suggesting SphK2 and S1P as potential therapeutic targets in cancer cell [2123]. Our recent studies demonstrate that a selective SphK2 inhibitor K-145 reduces intracellular S1P [23], reduces specific histone acetylation in the nucleus of breast cancer cells [24], drastically attenuated breast cancer growth in a syngeneic mouse model [23]. Together, SphKs/S1P signaling is critical for growth and survival of estrogen receptor positive breast cancer cells, however the role of SphKs/S1P in TNBC and more importantly in metastatic breast cancer progression was not demonstrated before.…”
Section: Introductionmentioning
confidence: 99%
“…A selective and potent inhibitor of sphingosine kinase 1 (SphK1) PF-543 is not effective on original parental triple-negative MDA-MB-231 breast cancer cells to attenuate survival signaling but it markedly attenuated cell growth and PI3K/AKT, ERK & p38 MAP kinases survival signaling of lung metastatic variant LM2-4 human breast cancer cells. We found that SphK2, which is mainly localized in the nucleus of triple-negative MDA-MB-231 human breast cancer cells [24], it also essential for metastatic variant LM2-4 breast cancer cells growth and survival. Our studies demonstrated that triple-negative metastatic human breast cancer progression is dependent on SphKs/S1P signaling.…”
Section: Introductionmentioning
confidence: 99%